PENGARUH E-COMMERCE DAN PENGGUNAAN SISTEM INFORMASI AKUNTANSI DALAM PENGAMBILAN KEPUTUSAN UNTUK BERWIRAUSAHA - Anggi Pramiswari, Dewa Ayu; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi, 2017)
This study aimed to obtain evidence about the influence of e-commerce on the decision to entrepreneurship, the effect of the use of accounting information systems in decision making for entrepreneurship. This research was conducted at the Faculty of Economics and Business, University of Udayana. Data collection methods used in this research is survey method with questionnaire technique. The population in this study were students majoring in accounting non-regular forces in 2014 Faculty of Economics and Business University of Udayana who have status as an active student. The data used in this study are primary data obtained directly by distributing questionnaires to 187 respondents using purposive sampling technique. The data analysis used is multiple linear regression analysis. The results show that e-commerce has positive influence on the decision to entrepreneurship, accounting information systems use a positive influence on the decision to entrepreneurship.
Keywords: E-Commerce, Accounting Information Systems, Entrepreneurship